Extrasystoles: relationship with arterial thromboembolic complications - Olga A. Germanova; Andrei V. Germanov; Yurii V. Shchukin (Наука и инновации в медицине, 2022)
Aim to determine the relationship between extrasystoles (ES) and the development of arterial thromboembolic complications.